Pelatihan Intensif Metode Jibril dalam Meningkatkan Kualitas Pengajaran Guru TPQ - Munir , Samsul; Suhaimi , Ahmad; Zakariya, Mukhamad (Universitas Pangeran Diponegoro Nganjuk, 2022)
The purpose of this assistance is how to apply the Jibril Method teaching method in learning to read the Al-Qur'an. The impact of the change from this dedication included: TPQ teachers who previously used the sorogan method where after reading the volumes and the Qur'an the students were busy and free to play, but after changing to using the Jibril method the students were more focused and enthusiastic in recite the Koran because in the Jibril method it places more emphasis on the suitability and regularity of reading with the 'knock' code together. Technically the impact of the changes also occurred in (i) the increased understanding of Al-Qur'an teachers related to Jibril's learning method, teachers understood how varied the Al-Qur'an learning methods were, (ii) the quality of teaching and learning at TPQ could make students understand Qur'anic skills. TPQ Santri are increasingly interested in learning, because Jibril's method provides a fun method, (iii) Management is increasingly professional in TPQ.